Pengaruh Pajak Bumi dan Bangunan, Dana Alokasi Umum, dan Dana Alokasi Khusus Terhadap Belanja Modal Jaringan (BMJ) dengan Sisa Lebih Pembiayaan Anggaran (SILPA) sebagai Variabel Pemoderasi - Oktavia Nur Fatimah; Fatchan Achyani (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to analyze the influence of Land and Building Tax, General Allocation Fund, and Special Allocation Fund on Network Capital Expenditure (BMJ) in Regencies/Cities in the former Surakarta Residency. The data used in this study are secondary data, taken from the financial statements of the realization of the Regional Budget (APBD) from 2016 to 2023 for a period of eight years. The sampling method uses purposive sampling. The sample consists of 6 Regencies and 1 City of Surakarta, a total of 7 local governments. The analytical tool used to test the hypothesis is multiple linear regression analysis using SPSS version 26. The results of this study indicate that Land and Building Tax has no effect on Network Capital Expenditure. While General Allocation Fund and Special Allocation Fund have an effect on Network Capital Expenditure. The Budget Financing Surplus is able to moderate the relationship between General Allocation Fund and Network Capital Expenditure. Meanwhile, the Budget Financing Surplus is not able to moderate the relationship between Land and Building Tax and Special Allocation Fund on Network Capital Expenditure.